2020
DOI: 10.30574/gscbps.2020.12.1.0217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the foraging activity of Apis mellifera (Hymenoptera: Apidae) on increasing yields of Gossypium hirsutum (Malvaceae) in Djoumassi (Garoua, Cameroon)

Abstract: To evaluate the impact of the foraging behaviour of Apis mellifera in increasing boll and seed yields of Gossypium hirsutum, its pollination activities were studied in Garoua for two seasons, from September through October 2018 and 2019. Observations were made on 540 flowers divided into four treatments of which two were differentiated according to the presence or absence of flower protection regarding insect visits; the third was made of protected and opened flowers, to allow Apis mellifera visits and the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Similar behavior of the same bee species was reported in Bé labo (Centre region of Cameroon) [23]. On the other hand, in the Ngaoundere region, which is an area with high beekeeping activity and high honey production in Cameroon [60], it has been reported that the foraging workers of this domestic bee collect more nectar than pollen during the day [18,20]. When visiting a flower for pollen collection, Ap.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Similar behavior of the same bee species was reported in Bé labo (Centre region of Cameroon) [23]. On the other hand, in the Ngaoundere region, which is an area with high beekeeping activity and high honey production in Cameroon [60], it has been reported that the foraging workers of this domestic bee collect more nectar than pollen during the day [18,20]. When visiting a flower for pollen collection, Ap.…”
Section: Discussionsupporting
confidence: 60%
“…mellifera was the most frequent floricultural insect on V. unguiculata blooming flowers with 25.7% of occurrence during the two years of study. This observation is reminiscent of that reported in Cameroon by Kengni et al [59], Djonwangwe et al [37], Mbianda et al [23], Adamou et al [20,37]. In Benin, the most frequent insect on cowpea flowers was reported as X. olivacea [34] while in Nigeria, Ap.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation